Correction: Brønsted acid mediated covalent organic framework membranes for efficient molecular separation. Issue 47 (25th November 2019) - Wang, Hongjian; Chen, Long; Yang, Hao; Wang, Meidi; Yang, Leixin; Du, Haiyan; Cao, Chenliang; Ren, Yanxiong; Wu, Yingzhen; Pan, Fusheng; Jiang, Zhongyi
Abstract : Correction for 'Brønsted acid mediated covalent organic framework membranes for efficient molecular separation' by Hongjian Wang et al., J. Mater. Chem. A, 2019, 7, 20317–20324.